The Correlation between Student’s Motivation in Choosing English Education Study Program at Universitas Negeri Padang and Student’s Learning Achievement in Microteaching Class - Yunis, Anita; Putri, Nofrina Eka (Journal of English Language Teaching, 2024)
Every person has their motivation in choosing something, and so do the students who have graduated from high school. The students might choose an English education Program Study as their major in a university. The choosing major can be influenced by what kinds of motivation they have, there are five kinds of motivation in this research: intrinsic, extrinsic, instrumental, integrative, and altruistic. Furthermore, since the major is related to the education field, the English education curriculum will have a Microteaching class as a subject that trains the education-based students to feel how teaching situations look. Hence, this research aims to find out what motivation types motivate the students the most to choose English education and how it correlates with students' English learning achievement in Microteaching classes. There are 31 participants from the same program study in entry year 2020, who have taken Microteaching class in this research. To collect the data, a questionnaire with 25 statements and a document about students’ results in Microteaching classes were used in this study. Then, the method used in this research was the correlational method. The findings of this study stated that the highest motivation type that motivated students to choose English Education was intrinsic. Yet, the correlation between students’ motivation in choosing English Education and students’ learning achievement in micro-teaching classes was displayed in a low level of correlation.